Insights into the structure–function relationship of brown plant hopper resistance protein, Bph14 of rice plant: a computational structural biology approach. Issue 7 (3rd May 2019) - Gupta, Manoj Kumar; Vadde, Ramakrishna; Donde, Ravindra; Gouda, Gayatri; Kumar, Jitendra; Nayak, Subhashree; Jena, Mayabini; Behera, Lambodar
Abstract : Brown plant hopper (BPH) is one of the major destructive insect pests of rice, causing severe yield loss. Thirty-two BPH resistance genes have been identified in cultivated and wild species of rice Although, molecular mechanism of rice plant resistance against BPH studied through map-based cloning, due to non-existence of NMR/crystal structures of Bph14 protein, recognition of leucine-rich repeat (LRR) domain and its interaction with different ligands are poorly understood. Thus, in the present study, in silico approach was adopted to predict three-dimensional structure of LRR domain of Bph14 using comparative modelling approach followed by interaction study with jasmonic and salicylic acids. LRR domain along with LRR-jasmonic and salicylic acid complexes were subjected to dynamic simulation using GROMACS, individually, for energy minimisation and refinement of the structure. Final binding energy of jasmonic and salicylic acid with LRR domain was calculated using MM/PBSA. Free-energy landscape analysis revealed that overall stability of LRR domain of Bph14 is not much affected after forming complex with jasmonic and salicylic acid. MM/PBSA analysis revealed that binding affinities of LRR domain towards salicylic acid is higher as compared to jasmonic acid. Interaction study of LRR domain with salicylic acid and jasmonic acid reveals that THR987 of LRR form hydrogen bond with both complexes. Thus, THR987 plays active role in the Bph14 and phytochemical interaction for inducing resistance in rice plant against BPH. In future, Bph14 gene and phytochemicals could be used in BPH management and development of novel resistant varieties for increasing rice yield.